Perpetual Struggle for Freedom: Examining the Dynamics of Afghans Migration to Iran Post-Taliban Takeover - Mulia, Jalaluddin Rizqi; Bagaskoro, Triyasa Panji; Salam, Subulu (Jisiera: The Journal of Islamic Studies and International Relations, 2025)
This research explores the dynamics of migration to Iran following the resurgence of the Taliban in Afghanistan in 2021. By accommodating Push-Pull Theory as the analytical tool, this study examines the factors that have influenced this migration pattern of Afghans to Iran post-Taliban takeover. The study employs an approach of gathering data from sources such as academic literature, government records and news articles. It reveals that a significant number of Afghans migrate to Iran driven by their need for access to education, better economic opportunities and security reasons. This migration trend raises concerns, for both Afghanistan and Iran as it impacts stability and international migration policies. The data findings show that the number of Afghan immigrants continues to increase year over year, peaking in 2023. Moreover, this study finds that Iran, which previously pursued open-door policies to immigrants, has shifted to a more restrictive and discriminatory regulation towards Afghan migrants. In addition, concerning the multidimensional instability, this paper highlights the crucial agenda to prioritize the safety of refugees by multiple actors, particularly the state and civil society.